INFLAMMATORY MARKERS AS PREDICTORS OF EFFICACY OF BEVACIZUMAB AND TYROSINE KINASE INHIBITORS THERAPY IN METASTATIC NON-SMALL CELL LUNG CANCER PATIENTS - Vynnychenko, Oleksandr; Moskalenko, Yuliia (Eastern Ukrainian Medical Journal, 2024)
Introduction. An essential role in the formation and development of non-small cell lung cancer (NSCLC) is played by systemic inflammation, which indirectly affects neoangiogenesis, proliferation, disease recurrence, and tumor spreading and can modulate the response to medication therapy. Clinical monitoring of inflammatory markers may help predict the outcome of the disease and allow select the most suitable candidates for targeted therapy of metastatic NSCLC (mNSCLC).The study aimed to establish independent predictors of the efficacy of bevacizumab and tyrosine kinase inhibitors (TKIs) therapy affecting progression-free survival (PFS) and overall survival (OS) in mNSCLC patients.Materials and methods. One hundred nine patients with mNSCLC who received bevacizumab or TKI therapy at the Sumy Regional Clinical Oncology Center participated in the retrospective study. We obtained data on patients' age, gender, body mass index, smoking status, number of metastases and their localization, category T and category N, and the applied treatment regimen from primary medical records. Based on complete blood count and chemistry tests, inflammatory indices were calculated: neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), metastatic lung cancer index (ALI), prognostic nutritional index (PNI), systemic inflammation index (SII) and index of hemoglobin, albumin, lymphocytes, and platelets (HALP). ROC analysis was used to establish the predictive value of indices and cut-off values. The Kaplan-Meier method and the Log-rank test assessed the effect on survival. Multivariate Cox regression analysis was used to determine independent predictors of treatment efficacy.The results. SII demonstrated a statistically significant impact on PFS and OS. Patients with low SII had longer PFS (Log-rank 0.0016) and OS (Log-rank P=0.0083). Median PFS in patients with low SII was 9.8 months versus 7.0 months in patients with high SII. Median OS in patients with low SII was 13.9 months versus 9.1 months in patients with high SII. Smoking status (P=0.001), category N (P=0.034), and SII (P=0.018) can be considered independent predictors of PFS and OS. Patients with high SII, current and former smokers, and those whose category N is 2 or 3 have a worse prognosis.Conclusions. SII is an independent predictor of the efficacy of bevacizumab and TKI therapy affecting PFS and OS in mNSCLC patients. A low SII correlates with better survival and a favorable impact on patient outcomes. In addition to SII, smoking status and category N are independent predictors of survival.